EURASIP Journal on Embedded Systems - Sousa, Leonel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
The EURASIP Journal on Embedded Systems (EURASIP JES) is an international journal that serves the large community of researchers and professional engineers who deal with the theory and practice of embedded systems, particularly encompassing all practical aspects of theory and methods used in designing homogeneous as well as heterogeneous embedded systems that combine data-driven and control-driven behaviors. Original full and short articles, correspondence and reviews on design and development of embedded systems, methodologies applied for their specification, modeling and design, and adaptation of algorithms for real-time execution are encouraged for submission. Coverage includes wide range of topics that cover embedded systems such as complex homogeneous and heterogeneous embedded systems, multicore systems, time-predictable embedded systems, use of FPGAs for implementation and prototyping of systems on chip and accelerators, specification languages and tools for embedded systems, modeling and verification techniques, hardware/software trade-offs and codesign, new design flows, design methodologies and synthesis methods, platform-based design, component-based design, adaptation of signal processing algorithms to constrained implementation resources, rapid prototyping, computing structures and architectures for complex embedded systems, real-time operating systems, methods and techniques for the design of low-power systems, interfacing with the real world, novel application case studies and experiences; coverage does not exclude other interesting related and emerging topics like software defined radio. Example applications include wireless-based embedded systems, , speech processing, image and video processing, digital signal processing applications, applications in industrial control and automation, automotive sector, intelligent devices and environments, mechatronic systems. The journal is an Open Access journal since 2006. Professor Zoran Salcic was its Editor-in Chief from its foundation in 2005 till the end of 2014. Professor Leonel Sousa substituted him, and is leading the journal since January 2015. He invites all of you to submit the best of your work on embedded systems to the journal.
Keywords: Engineering; Microprogramming; Electronic circuits; Signal processing; Image processing; Speech processing systems; Engineering; Signal,Image and Speech Processing; Circuits and Systems; Control Structures and Microprogramming; Electronic Circuits and Devices